Planktonic and epibenthic foraminifera oxygen and carbon stable isotope data, sediment weights and sediment geochemistry data for off-splice samples from IODP Site 339-U1387 in the Gulf of Cadiz - Voelker, Antje H L; Rodrigues, Teresa (PANGAEA, 2025)
When generating high resolution paleoceanographic reconstructions for the early to middle Pleistocene sections of Integrated Ocean Drilling Program (IODP) Site U1387, it became obvious that proxy data misfits existed at most splice transitions in the shipboard splice below ~155 mcd. A revised splice was established below Core U1387B-18X based on X-ray fluorescence (XRF) derived element records (e.g., ln(Fe/Ca)) and the stable isotope records obtained for planktonic and benthic foraminifers (Voelker et al., 2018; doi: 10.2204/iodp.proc.339.204.2018). Corrections were needed at most of the splice transitions below Core U1387A-19X with adjustments ranging from a few centimeters to several meters, leading to a corrected meters composite depth (c-mcd) scale. In addition, Core U1387A-33X and sections of Core U1387A-36X were integrated into the revised splice to replace Core U1387C-2R and sections of Core U1387C-5R, respectively. The substitution of Core U1387C-2R with Core U1387A-33X is an option for the intended paleoceanographic research and not essential for lower resolution studies. Since data for samples outside the revised splice sequence will not be included in future publications, we are making the data, in particular of Cores U1387C-2R and U1387C-5R, available, so that it can be used by those working along the shipboard splice or needing such data for other interests. Consequently, this dataset provides the stable isotope data measured in G. bulloides and two epibenthic foraminifera species, the sample's dry weight and sand fraction related data as well total organic carbon, carbonate, C/N and lipid biomarker extraction derived data, where available, for Core U1387C-2R and parts of Core U1387C-5R as well as from a few other samples that are not part of the revised splice sequence.
Keywords: Gulf of Cadiz; lipid biomarkers; Stable carbon and oxygen isotopes; Total Carbonate; Total organic carbon (TOC)